EL SISTEMA EDUCATIVO CHILENO FOMENTA LA DESIGUALDAD - Muñoz, Vernor (La Sociología en sus Escenarios, 2012)
Abstract. A research of UNESCO concluded that the CHILEAN EDUCATIVE SYSTEM " it is oriented by processes of privatización" and it is translated in " segmentation, exclusion and discriminación" , UNESCO said. The organism remembered that tried international they force Chile to look for " gradually the gratuity in the secondary education and universitaria". The study realized an analysis of the educative systems from its main axes - Availability, Accessibility, Acceptability and Adaptability including a revision of the conceptual frame of the right to the education, defined by international treaties that Chile has subscribed, emphasizing the general and specific obligations of the State regarding the education. The study emphasizes that the legislations of Argentina and Uruguay " They are very explicit in restricting any possibility of merchandizing the education, even prohibiting the international treaty subscription that they facilitate that the education is dealed with like a "bien de consumo". Resumen. Investigación de la Unesco concluyó que EL SISTEMA EDUCATIVO CHILENO "está orientado por procesos de privatización" y ello se traduce en "segmentación, exclusión y discriminación", dijo Unesco. El organismo recordó que tratados internacionales obligan a Chile a buscar "gradualmente la gratuidad en la educación secundaria y universitaria". El estudio realizó un análisis de los sistemas educativos a partir de sus principales ejes -DISPONIBILIDAD, ACCESIBILIDAD, ACEPTABILIDAD Y ADAPTABILIDAD- incluyendo una revisión del marco conceptual del derecho a la educación, definido por tratados internacionales que Chile ha suscrito, subrayando las obligaciones generales y específicas del Estado relativas a la educación. El estudio destaca que las legislaciones de Argentina y Uruguay "son muy explícitas en restringir cualquier posibilidad de mercantilizar la educación, incluso prohibiendo la suscripción de tratados internacionales que faciliten que la educación sea tratada como un bien de consumo".